Development of TPACK Based Learning Media on Ablution Material to Increase Student Understanding - Fusvita Dewi; Neysa Vania Nasution; Wahyuddin Nur Nasution; Nirwana Anas; Ahmad Mustaqim (Pusdikra-Publishing.com, 2023)
This research aims to develop TPACK (Technological Pedagogical Content Knowledge) based learning media on ablution material with the aim of increasing students'understanding. TPACK uses an approach that integrates technology, pedagogy and content knowledge to create effective learning experiences. The research method used is development research with the ADDIE model. The subjects in this research were 20 people. Data collection techniques were obtained through validation tests, practicality tests and effectiveness tests by expert people. Data collection instruments using questionnaires and student responses. The results of the research show that the development of TPACK-based learning media on ablution material is effective in increasing students' understanding. Students show improvement in understanding the steps of ablution, the meaning of the associated symbols and the relevance of daily life practices. This research contributes to the development of a learning model that can be adopted in the context of religious education, especially regarding ablution material. This learning media helps students understand the procedures for ablution so that they gain a valid, practical and effective understanding.